Functional metal oxide photocatalyst for efficient carbon dioxide reduction - Liao, Yusen (2016)
Solar fuels derived from solar energy are envisioned to replace fossil fuels for a sustainable earth and society. Photocatalytic carbon dioxide (CO2) reduction for gaseous or liquid fuels production is one of the most promising processes to not only solve the energy crisis, but also reduce the environmental issues such as greenhouse effect. However, advancement of CO2 reduction for solar fuels production is largely hindered by the lack of efficient photocatalysts. In this thesis, the work was focused on surface modification of semiconductor metal oxide photocatalyst to increase the affinity between CO2 and catalysts as well as preventing the electron hole pair recombination toward optimize the reaction efficiency.